Evaluation of Failure Pressure for Gas Pipelines with Combined Defects - Tadas Vilkys; Vitalijus Rudzinskas; Olegas Prentkovskis; Jurijus Tretjakovas; Nikolaj Višniakov; Pavlo Maruschak (Metals, 2018)
The paper presents the study of the influence of mechanical damage on the safe operation of gas transmission pipelines. The main types of pipeline damage with the actual parameters and their influence on the operational parameters are analysed. The damaged fractures of the section of the pipeline Kaunas (Lithuania)–Kaliningrad (Russia) were investigated in the laboratory. The main operational characteristics and the structure of the pipeline’s metal after the period of long-term operation were determined using various research and experimental methods. The influence of the pipeline’s damage was modelled by using the Finite Element Method and the ANSYS code. The predictions of the failure pressure were made, taking into consideration the actual properties of the pipeline’s metal. Techniques including the hardness and microhardness measurement, chemical analysis, the impact strength test, and metallography analysis with an optical microscope, were used in the experimental study.